Code Switching and Gender in SMS Texting among Algerian University Students. The Case Of 4th Year Students of English, Department of English, University of Algiers 2 - Nora Achili (The Journal of Studies in Language, Culture and Society, 2019)
The paper at issue addressed the nature of SMS messaging by focusing on gender differences in terms of code switching types’ use, on the one hand, and differences in language choice among male and female texters, on the other hand. The study consisted of the examination of a corpus of 120 messages sent by Algerian 4th year students of English belonging to a multilingual context in an attempt to identify instances of code switching and language use in their messages. The results highlighted the occurrence of two types of code switching namely: Extrasentential and Intrasentential switching types, with the last mentioned as the most frequent type. In terms of gender, the results showed significant differences in code switching behaviours between males and females, with females code switching much more, on the one side, and using Intrasentential code switching type more, on the other side. Conversely, Extrasentential code switching type was absent in both groups’ messages. In terms of language use, English was the most frequently utilized language by both male and female texters. Despite the fact that both sexes use English in their messages, the data showed significant disparities in language use among male and female texters.